Synthesis, characterisation and biological activities of S-2- or S-4-methylbenzyl-β-N-(di-2-pyridyl)methylenedithiocarbazate and Cu(II), Ni(II), Zn(II) and Cd(II) complexes. (5th September 2017) - Ravoof, T.B.S.A.; Crouse, K.A.; Tiekink, E.R.T.; Tahir, M.I.M.; Yusof, E.N.Md.; Rosli, R.
Graphical abstract: The article describes the synthesis and characterisation of isomeric Schiff bases derived from S-R-methylbenzyldithiocarbazate (R = 2, 3, 4) and di-2-pyridyl ketone (referred to as NNS′, NNS″, NNS‴); and their metal complexes of general formula, [M(NNS)2 ] (M = Cu(II), Ni(II), Zn(II) and Cd(II). They have been characterised by various spectro-analytical techniques. The crystal structures of [Ni(NNS′)2 ], [Ni(NNS‴)2 ] and [Cd(NNS′)2 ] were solved via single-crystal X-ray crystallographic analysis where all three complexes possessed a distorted octahedral geometry. The complexes have been assayed against selected pathogens where they were inactive against all the fungal strains tested, but were mildly active against Bacillus subtilis . The Schiff bases and their transition metal complexes were also mostly inactive against the examined cancer cell lines MCF-7 and the MDA-MB-231. Cytotoxic activity was observed to be enhanced upon complexation, particularly for the Ni(II) complexes. Abstract: Metal complexes of general formula, [M(NNS)2 ] (M = Cu(II), Ni(II), Zn(II) and Cd(II); NNS′ = S-2-methylbenzyl-β-N-(di-2-pyridyl)methylenedithiocarbazate (1 ), NNS″ = S-3-methylbenzyl-β-N-(di-2-pyridyl)methylenedithiocarbazate (2 ) and NNS‴ = S-4-methylbenzyl-β-N-(di-2-pyridyl)methylenedithiocarbazate (3 ) have been synthesized by reacting the respective metal acetates with the Schiff bases in an ethanol/acetonitrile mixture. They have been characterised by various physico-chemical techniques. Magnetic and spectral evidence indicate the formation of six-coordinate complexes in which the Schiff base coordinates as a uninegatively charged tridentate NNS ligand. The crystal structures of [Ni(NNS′)2 ] (5 ), [Ni(NNS‴)2 ] (13 ) and [Cd(NNS′)2 ] (7 ) were solved via single-crystal X-ray crystallographic analysis. All three complexes possess a distorted octahedral geometry where two Schiff bases are coordinated to the central metal ion via the pyridine nitrogen-atom, the azomethine-nitrogen atom and the thiolate-sulphur atom; like donor atoms in the N4 S2 donor set are mutually trans . The complexes have been assayed against selected pathogens and cancer cell lines. The complexes were inactive against all the fungal strains tested, but were mildly active against the bacterial strains tested, especially against Bacillus subtilis . Anti-microbial activity generally improved upon complexation with the transition metal ions. The Schiff bases and their transition metal complexes were mostly inactive against the examined cancer cell lines. The Schiff bases1 –3 were inactive against the MCF-7 (Human Breast cancer cells with positive estrogen receptor) and the MDA-MB-231 (Human Breast cancer cells with negative estrogen receptor) cell lines. Only9 was active against MCF-7 whereas10 and13 were active against the MDA-MB-231 cell line. Cytotoxic activity was observed to be enhanced upon complexation particularly for the Ni(II) complexes.